Effects of tapentadol on pain, motor symptoms and cognitive functions in Parkinson’s disease - Freo, Ulderico (J Pain Res, 2018)
BACKGROUND: Pain is a common and undertreated non-motor symptom in patients with Parkinson’s disease (PD). Opioids have been seldom used in PD because they could worsen cognitive and motor functions. OBJECTIVE: We aimed to assess efficacy and tolerability of tapentadol in PD patients. METHODS: We retrospectively reviewed 21 PD patients treated with tapentadol extended release (ER) for chronic pain. Patients were evaluated before treatment and at 3 and 6 months during treatment for pain intensity (current, 24-hour average, and minimum and worst) with a 0–10 Numerical Rating Scale and the painDETECT questionnaire; for motor symptom severity with the Unified PD Rating Scale part III and the Hoehn and Yahr scale; for cognitive functions with Mini-Mental Status Examination, Corsi’s Block-Tapping test, Digit Span test, Digit-Symbol Substitution test, FAS test, Rey’s Auditory Verbal Learning test, Trail-Making test A and B and the 9-Hole Peg test; for anxiety and depression with the Hospital Anxiety and Depression Scale; and for the quality of life with the Short Form-12. Data were analyzed by 1-way analysis of variance and paired t-test, and by Friedman’s and Wilcoxon’s tests. Statistical significance was taken in all cases as P<0.05. RESULTS: Pain intensity decreased over the course of treatment. No differences were found in PD symptom severity and dopaminergic drug dosages between pretreatment and treatment evaluations. No decrement in cognitive neuropsychological performances was found and an improvement was observed in Digit Span test, Digit-Symbol Substitution test, and FAS test. The levels of anxiety, depression, and quality of life improved. Overall, tapentadol ER was well tolerated and most patients reported no or mild and short-lived gastroenterological and neurological side effects. CONCLUSION: These results indicate the potential efficacy and tolerability of medium–high doses of tapentadol ER for the treatment of pain in PD.